Surto de malária induzida entre usuários de drogas injetáveis Outbreak of malaria among injectable-drug users - Luiz Carlos Barradas Barata; Maria Tereza M. Andriguetti; Marina Ruiz de Matos (Universidade de São Paulo, 1993)
Em julho de 1990, foi registrado na cidade de Bauru, Estado de São Paulo, Brasil, um surto de malária envolvendo usuários de cocaína injetável. Uma ampla investigação epidemiológica, conduzida de 19 de julho a 13 de setembro, revelou que pelo menos 119 pessoas estavam envolvidas no surto, uma vez que haviam compartilhado seringas e agulhas com um ou mais casos confirmados nos 3 meses anteriores à ocorrência. Cento e duas dessas pessoas foram localizadas e entrevistadas, e destas, 99 foram submetidas a exame de gota espessa e 91 a exames sorológicos para malária. Foram confirmados por exame hemoscópico 21 casos de malária por P. vivax, e 3 outros tiveram exame sorológico positivo para P. vivax. O controle da transmissão foi obtido fornecendo-se cloroquina aos envolvidos no surto, numa dose inicial de 10 comprimidos, seguida de doses supressivas semanais de 2 comprimidos até que fosse identificado o último comunicante. Amostras de soro coletadas na ocasião revelaram, ao lado da malária, uma alta prevalência de infecções pelo HIV (58%) e pelo vírus da hepatite B (40%). Foram discutidas as dificuldades para o controle do surto e a possibilidade da malária vir a se tornar uma doença endêmica entre usuários de drogas injetáveis, no Estado de São Paulo. Five cases of malaria were detected among cocaine users by the local health service in Bauru, a city with a population of 260,000, located 324 km from S. Paulo, Brazil, during the first three weeks of July 1990. Autochthonous malaria had not occurred in Bauru since 1978, and all the five cases denied having recently traveled to endemic areas. An extensive epidemiologic survey conducted from July 19 to September 13 revealed that the 5 cases were in fact part of a malaria outbreak among endovenous drug users. Moreover, at least 114 other people, who had in the last three months shared syringes and needles with one or more proved cases, were also involved in the outbreak. One hundred and two people were identified and interviewed orally. The examination of thick smears made from samples collected from 99 of them confirmed 21 cases of vivax malaria. Three people with negative blood smears had an indirect imunofluorescent assay positive to P. vivax antigen. Although the index case could not be discovered, the investigation suggested that one or more people who had recently traveled to the Amazon region might have introduced the disease. The control of the outbreak was achieved after offering treatment with chloroquine (10 tablets) to confirmed cases and contacts, followed by weekly suppresive chloroquine (2 tablets) until the last contact was detected. Malaria examination of 91 blood samples also revealed a high prevalence of hepatitis B virus infection (40%) and HIV infection (58%) among those involved in the outbreak. The strategy used to identify the cases and the contacts and the difficulties overcome in carrying it through are described. It is also suggested that malaria might become an endemic disease among endovenous drug users in the State of S. Paulo.